(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Speakers do not always express only their own thoughts; sometimes, they incorporate someone else’s speech into their own discourse. There are various ways to present another person’s speech, and the best examples are direct and indirect speech. The use of someone else’s opinion in the form of an independent sentence together with the author’s speech while preserving the lexical, grammatical and semantic features of the opinion of other people is called an indirect sentence. On the other hand, a direct speech is when the author restates someone else’s words while retaining the content, but adopting their lexical, grammatical, and semantic characteristics. This article discusses the specific features of direct and indirect speech in Uzbek and French